Static Analysis of Steel Plates and Sections Retrofitted with FRP Plates by Finite Elements Modelling - Hossein Amoushahi (Iranian Society of Structrual Engineering (ISSE), 2019)
Nowadays the use of FRP composites for strengthening steel structures has been considered by researchers. In present study, The maximum deformation of steel plates and structural sections before and after strengthening by GFRP plates was evaluated by modelling and static analysis using ABAQUS finite element software. The results indicated the amount of increasing rate in stiffness and load capacity of studied steel plates and I-shaped beams. In this strengthening method, better results would be achieved by installing GFRP plates to the flange of the beam in comparison with installing them to the web of the beam. The results for studied steel hollow sections and I-shaped columns, comparing axial and lateral behaviour of specimens before and after strengthening indicates the increasing rate in axial stiffness and therefore increase in load carrying capacity of columns in comparison with bare specimens. In this research, the influence of geometric imperfection on the reduction of the limit loads of the bare as well as the retrofitted steel plates was also evaluated. The results indicated that the strengthening of steel plates with GFRP plates could be decreased by the sensitivity of them due to presence of initial geometric imperfections, particularly for plates with higher width-to-thickness ratio.